Real time analysis of Intelligent placing system for vehicles using IOT with Deep learning. (2022) - Jaiswal, Sushma; Kumar Sharma, Dilip; Jaiswal, Tarun; Basumatary, Bhimraj; Tiwari, Mohit; Tiwari, Tripti
Abstract: There is an enormous in number of vehicles in last few years. So, it becomes important to make effective use of technology to enable inconvenience free parking at public and/or private places. In traditional placing systems, drivers face difficulty in finding available placing slots. These systems ignore the fact of placing the vehicles on roads, time management in peak hours, wrong parking of a vehicle in a placing slot. Moreover, the traditional systems require more human intervention in a placing zone. To deal with above said issues, there is an urgent requirement of developing Real Time Intelligent placing system. In this proposed system a Real Time Intelligent placing system based on IOT and Deep learning techniques to answer the real time management of placing and uncertainties. The proposed solution utilizes smart sensors, cloud computing and cyber physical system. Development of graphical user interface for administrator and end-user is a major challenge as it requires ensuring smooth monitoring, control and security of placing system. Moreover, it needs to establish effortless coordination with an end-user. The proposed system is successful in smartly addressing the challenges such as indicating status of placing slot well in advance to end-user, use of reserved and unreserved placing slots, wrong placing, unauthorized placing, real time analysis of free and occupied slots, detecting multiple objects in a placing slot such as bike in car slot, fault detection in one or more components and traffic management during peak hours. The system reduces the human work, saves time, money and energy.